2012
DOI: 10.1007/s10827-012-0387-7
|View full text |Cite|
|
Sign up to set email alerts
|

Coupled left-shift of Nav channels: modeling the Na+-loading and dysfunctional excitability of damaged axons

Abstract: Injury to neural tissue renders voltage-gated Na⁺ (Nav) channels leaky. Even mild axonal trauma initiates Na⁺-loading, leading to secondary Ca²⁺-loading and white matter degeneration. The nodal isoform is Nav1.6 and for Nav1.6-expressing HEK-cells, traumatic whole cell stretch causes an immediate tetrodotoxin-sensitive Na⁺-leak. In stretch-damaged oocyte patches, Nav1.6 current undergoes damage-intensity dependent hyperpolarizing- (left-) shifts, but whether left-shift underlies injured-axon Nav-leak is uncert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
156
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(166 citation statements)
references
References 74 publications
8
156
2
Order By: Relevance
“…This Na v (and in this model, K v ) leak has been rationalized by a hyperpolarizing shift (or left-shift) of transient current operational range (Wang et al 2009) in the conductance of the ion channel. Boucher et al (2012) proposed to capture this stretchinduced alteration by left-shifting the potential for Na v channels' activation and inactivation variables in the damaged part of the nodal axolemma. Despite the fact that such blebbing should a priori affect equally all types of ion channels, previous attempts to consider the leak of K v have not been fully pursued (Boucher et al 2012).…”
Section: Damage Coupling Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…This Na v (and in this model, K v ) leak has been rationalized by a hyperpolarizing shift (or left-shift) of transient current operational range (Wang et al 2009) in the conductance of the ion channel. Boucher et al (2012) proposed to capture this stretchinduced alteration by left-shifting the potential for Na v channels' activation and inactivation variables in the damaged part of the nodal axolemma. Despite the fact that such blebbing should a priori affect equally all types of ion channels, previous attempts to consider the leak of K v have not been fully pursued (Boucher et al 2012).…”
Section: Damage Coupling Modelmentioning
confidence: 99%
“…Boucher et al (2012) proposed to capture this stretchinduced alteration by left-shifting the potential for Na v channels' activation and inactivation variables in the damaged part of the nodal axolemma. Despite the fact that such blebbing should a priori affect equally all types of ion channels, previous attempts to consider the leak of K v have not been fully pursued (Boucher et al 2012). It has actually been suggested that the observed extracellular K + accumulation in post-traumatic rat hippocampal slices would be due to glial activity and not neuronal leak (D'Ambrosio et al 1999).…”
Section: Damage Coupling Modelmentioning
confidence: 99%
See 3 more Smart Citations